Nuclear alignment: Classical dynamical model for the -238238U system - Sharma, S. Shelly [UNESP]; Galetti, D. [UNESP] (American Physical Society (APS), 1992)
Dynamical properties of the -238238U system at the classical turning point, specifically the distance of closest approach, the relative orientations of the nuclei, and deformations have been studied at the sub-Coulomb energy of Elab=6.07 MeV/nucleon using a classical dynamical model with a variable moment of inertia. Probability of favorable alignment for anomalous positron-electron pair emission through vacuum decay is calculated. The calculated small favorable alignment probability value of 0.116 is found to be enhanced by about 16% in comparison with the results of a similar study using a fixed moment of inertia as well as the results from a semiquantal calculation reported earlier. © 1992 The American Physical Society.